2015
DOI: 10.1016/j.jad.2015.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial prefrontal cortex thinning in preschool-onset depression

Abstract: Background The ventromedial prefrontal cortex (VMPFC) is a key center of affect regulation and processing, fundamental aspects of emotional competence which are disrupted in mood disorders. Structural alterations of VMPFC have consistently been observed in adult major depression and are associated with depression severity, yet it is unknown whether young children with depression demonstrate similar abnormalities. We investigated cortical thickness differences in the VMPFC of children with a history of preschoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 57 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…In adults, major depressive disorder (MDD) tends to be linked with decreased CT in PFC regions, although areas of thickening have been found ( Lener et al, 2016 ; Peterson et al, 2009 ; Schmaal et al, 2016 ; Tu et al, 2012 ; van Eijndhoven et al, 2013 ). Similarly, some studies of pediatric MDD have indicated decreased CT in PFC regions ( Marrus et al, 2015 ; Peterson et al, 2009 ) (see Supplementary Table S2). In addition, in a longitudinal neuroimaging study, greater depressive symptoms or an MDD diagnosis at 3–6 years of age was associated with an increased rate of global cortical thinning across middle childhood and into early adolescence ( Luby et al, 2016 ).…”
Section: Introductionmentioning
confidence: 81%
“…In adults, major depressive disorder (MDD) tends to be linked with decreased CT in PFC regions, although areas of thickening have been found ( Lener et al, 2016 ; Peterson et al, 2009 ; Schmaal et al, 2016 ; Tu et al, 2012 ; van Eijndhoven et al, 2013 ). Similarly, some studies of pediatric MDD have indicated decreased CT in PFC regions ( Marrus et al, 2015 ; Peterson et al, 2009 ) (see Supplementary Table S2). In addition, in a longitudinal neuroimaging study, greater depressive symptoms or an MDD diagnosis at 3–6 years of age was associated with an increased rate of global cortical thinning across middle childhood and into early adolescence ( Luby et al, 2016 ).…”
Section: Introductionmentioning
confidence: 81%
“…Dysfunction caused by dlPFC damage in stroke is considered a predisposing factor to poststroke depression [ 56 ]. In addition, a decrease of cortical thickness in the right vmPFC, which occurs in the early stages of neurodevelopment, results in depression in preschoolers [ 57 ]. Volume reduction of the prefrontal cortex may result from the disruption and atrophy of neurons and glia in depression, as observed in the hippocampus [ 21 , 22 ].…”
Section: The Prefrontal Cortex In Depressionmentioning
confidence: 99%
“…There have been several studies that investigated neural correlates of currently depressed preschoolers 71,72 and in children/adolescents with a history of preschool depression 52,7381 . For example, one study used functional magnetic resonance imaging (fMRI) to examine functional brain activity and its relationship to emotion regulation in n=23 currently depressed, 4–6 year old preschoolers and n=31 matched, healthy preschoolers 71 .…”
Section: Neurobiological Correlates Of Preschool Depressionmentioning
confidence: 99%